Impact of age on viral kinetics of peginterferon alfa‐2a/ribavirin in chronic hepatitis C: final analysis from the PROPHESYS cohort. Issue 5 (17th October 2013) - Aronsohn, A.; Ancuta, I.; Caruntu, F.; Coppola, C.; Delic, D.; Digiacomo, A.; Dusheiko, G. M.; Lengyel, G.; Marcellin, P.; Orlandini, A.; Pruthi, J.; Silva, G. F.; et al.
Summary The population of patients with chronic hepatitis C viral infection is ageing; however, elderly, hepatitis C‐infected patients are understudied and less frequently treated. This subanalysis of data from the multinational PROPHESYS study examined associations between age (≤65 vs >65 years), on‐treatment virological response and sustained virological response (SVR) in patients treated with peginterferon alfa‐2a (40KD)/ribavirin in accordance with local licences. PROPHESYS comprised three cohorts studied in 19 countries according to country‐specific legal and regulatory requirements. This subanalysis includes treatment‐naive HCV mono‐infected patients assigned to receive peginterferon alfa‐2a (40KD)/ribavirin, with 6276 individuals aged ≤65 years and 349 aged >65 years. Rapid virological response (RVR) rates by Week 4 were consistently lower in older genotype (G) 1 (21.6% vs 27.2% in younger patients), G2 (80.7% vs 85.1%) and G3 (60.0% vs 74.2%) patients. SVR rates were significantly lower (29.8% vs 43.0%) and relapse rates significantly higher (43.1% vs 26.7%) in older G1 patients (P = 0.0002 vs ≤65 years). In contrast, SVR and relapse rates were similar in G2 and G3 patients regardless of age. The positive predictive value of RVR for SVR was comparable in older and younger G1 patients (66.7% vs 68.6%, respectively) and higher in older G2 (80.7% vs 75.6%) and G3 (77.8% vs 66.8%) patients. Virological response rates are generally lower in elderly CHC patients, and RVR is a reliable positive predictor of SVR in patients >65 years.